Provider Training in the Management of Headache Following Concussion Clinical Recommendation: Promoting a Standardized Means for Efficient Patient Recovery and Timely Return to Duty - Remigio-Baker, Rosemay A.; Kiser, Seth; Ferdosi, Hamid; Gregory, Emma; Engel, Scot; Sebesta, Sean; Beauchamp, Daniel; Malik, Saafan; Scher, Ann; Hinds, Sidney R. (Frontiers in Neurology, 2020)
Background: Headache is a common symptom reported following concussion/mild traumatic brain injury. The Department of Defense’s clinical recommendation (CR) describes guidance for primary care providers for the management of post-traumatic headache (PTH) in Service Members. Objective: The objective of this study is to examine the association between training on the CR with provider clinical practice, patient behaviors and symptom recovery. Methods: Participants were healthcare providers and two patient groups (one receiving care as usual [CAU] and another receiving care after provider training on PTH CR [CR+]). Providers were interviewed at three time points: 1) prior to CAU enrollment; 2) after CAU enrollment, but prior to training; and 3) after CR+ follow-up. Data from the second and third provider interview were used to evaluate a potential difference between provider practices pre- and post-training (n=13). Patients were enrolled within 6 months of concussion. Patient outcomes (including neurobehavioral and headache symptoms) were assessed at three time-points: within 72 hours (n=35), at 1-week (n=34) and at 1-month post-enrollment (n=27). Results: Most follow-up care reported by providers were recommended within 72 hours of initial visit post-training vs. >1 week pre-training. Additionally, providers reported a greater number of visits based on patient symptoms after training than before. Post-training, most providers reported referring patients to higher level of care ‘as needed’, if not ‘very rarely’, compared to 25% reported referrals prior to training. At 1-week post-enrollment the CR+ patient group reported more frequent medical provider visits compared to the CAU group. This trend was reversed at the 1-month follow-up whereby more CAU reported seeing a medical provider compared to CR+. By 1-week post-enrollment, fewer patients in the CR+ group reported being referred to any other providers or specialists compared to the CAU group. No differences in patient outcomes by provider training was found. Conclusion: The study results demonstrate the feasibility of training on the Management of Headache Following Concussion CR in order to change provider practices by promoting timely care, and promoting patient compliance as shown through improvement in follow-up visits and more monitoring within the primary care clinic.